Ultimate Load of Different Types of Reinforced Self-Compacting Concrete Columns Attacked by Sulphate - N. Muhammed; L. Shihab; S. Sakin (Salehan Institute of Higher Education, 2022)
In this study, the effects of the partial immersion of sulphate attack on the ultimate load capacity of reinforced self-compacting concrete (SCC) columns and the sulphate attack resistance improvement using silica fume, steel fibres, and the combination of silica fume and steel fibres were assessed. Twelve short circular self-compacting reinforced concrete columns (0.150 m in diameter and 0.7 m long) were cast and divided into groups according to (1) the three acid-attack groups. The first group was tested without an acid attack (control). The second group was tested after 1 month of exposure to 2% acid. The final group was tested after 1 month of exposure to 4% acid and was then (2) subdivided according to the type of casted concrete. The first group was cast with SCC. The second group was cast with SCC and silica fume (0.1% of the cement weight). The third group was cast with SCC and 1% volume fraction steel fibres. The fourth group was cast with SCC silica fume and 1% volume fraction steel fibre. All columns were tested by axial loading. The ultimate load was increased by 42% with silica fume, 190% with steel fibres, and 238% with silica fume and steel fibres. Exposure to 2% and 4% acid reduced the ultimate loads of the columns casted with SCC by 23% and 47%, the columns casted with SCC and silica fume by 34% and 37%, the columns casted with SCC and steel fibres by 69% and 78%, and the columns casted with SCC, silica fume, and steel fibres by 72% and 79%, respectively. Based on the results, using silica fumes improved sulphate resistance, and using steel fibres enhanced sulphate resistance at an acceptable ratio. Furthermore, the mix with silica fume and steel fibres improved sulphate resistance at a good ratio. We encountered several problems in this study. The partial immersion of sulphate affected the strain in both concrete and steel. Future studies using different immersion ratios are recommended. Doi: 10.28991/CEJ-2022-08-10-04 Full Text: PDF